Japan-American diplomatic relations in the meiji-taisho era - Hikomatsu, Kamikawa (Pan-Pacific, 1958)
This book consists of the following four parts: The last stage of the shogunate from the opening of the country to the meiji restoration; The first half of meiji from the restoration through the treaty of shimonoseki; The latter half of the meiji the period between the tripartite intervention and the manchurian railway problems; The taisho ear the immigration act and world war one.